2017
DOI: 10.1021/acs.analchem.7b00331
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of Mass Spectral Interferences of Chlorinated Alkanes and Their Thermal Degradation Products: Chlorinated Alkenes

Abstract: Chlorinated paraffins (CPs) are high production volume chemicals and ubiquitous environmental contaminants. CPs are produced and used as complex mixtures of polychlorinated n-alkanes containing thousands of isomers, leading to demanding analytical challenges. Due to their high degree of chlorination, CPs have highly complex isotopic mass patterns that often overlap, even when applying high resolution mass spectrometry. This is further complicated in the presence of degradation products such as chlorinated alke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…Compared with the chlorine atoms of parent SCCPs, the dechlorination and chlorine rearrangement products were all identified by ECNI. 43 The selected parent SCCPs contained 10, 11, and 13 carbon atoms, respectively. However, the daughter chemicals included SCCPs containing 12 carbon atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the chlorine atoms of parent SCCPs, the dechlorination and chlorine rearrangement products were all identified by ECNI. 43 The selected parent SCCPs contained 10, 11, and 13 carbon atoms, respectively. However, the daughter chemicals included SCCPs containing 12 carbon atoms.…”
Section: Resultsmentioning
confidence: 99%
“…2,3,4,5,6,7heptachloroundedecane) remains unachieved by single-column GC or liquid chromatography (LC), resulting in a typical wide lump in the chromatogram and strong interference with other CPs such as medium-chain chlorinated paraffins (MCCPs) and compounds with similar retention times. Separation between congener groups, other fragmenting ions, and other compounds by mass spectrometry (MS) is difficult too, as at least a mass resolution of 20,000 (full width at half height) is needed [6]. For Cl 5 with electron-capture negative ionization MS (ECNI-MS) have a mass to charge ratio (m/z) of 395.9 and 396.1, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, mass spectrometers with a resolution below 10 000 FWHM are not able to resolve the commonly occurring mass interferences from different CP congener groups (for example interferences between 12 ) An increased response factor of the longer-chained CPs will increase this percentage even further. 74 In addition to the commonly occurring mass interferences, other mass interferences from, for example, transformation products 79 or unexpected fragment ions formed during the ionization can complicate the analysis even more. However, Schinkel et al 79,81 and Yuan et al 80 showed that it is possible to identify the target congeners when applying deconvolution procedures.…”
mentioning
confidence: 99%